Cash Management Practices and Corporate Sustainable Longevity: A Correlational Study on Retail SMEs in Davao City - Parpan, Mark Glenn; Quiroz, Althea Hart; Salanawon, Kimberly; Tandog, Shekinah Belle (Technium Social Sciences Journal, 2025)
Small and Medium-Sized Enterprises (SMEs) have faced consistently high closure rates worldwide. This raised the question of their ability to sustain longevity. Thus, this study aimed to examine the influence and relationship between cash management practices and corporate sustainable longevity of retail SMEs in Davao City. Using a descriptive-correlational research design, 304 retail SMEs were selected with a simple random sampling technique to meet the study objectives. Slovin’s Formula was used to calculate the required minimum respondents. A survey-based approach and a 5-point Likert Scale were employed to collect data, which was later analyzed using descriptive statistics, Pearson’s Correlation Coefficient (r), and Multiple Regression Analysis. The results revealed that Cash Management Practices have a direct and positive relationship with Corporate Sustainable Longevity in alignment with the Resource-Based View. Furthermore, all domains under Cash Management Practices have a significant influence on a business’ ability to last. Therefore, such foundational internal practices should be viewed as more than day-to-day tasks, as they are crucial in sustaining businesses over time.